2013
DOI: 10.1016/j.yebeh.2013.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence two years after epilepsy surgery in children

Abstract: Intelligence before and two years after epilepsy surgery was assessed in 94 children and adolescents and related to preoperative IQ and seizure outcome. The median full-scale IQ was 70 before and two years after surgery. The proportion with a higher or unchanged postoperative IQ was 24 of 49 (49%) of those with an IQ of 70 and more before surgery, nine of 17 (53%) of those with an IQ of 50-69, and ten of 28 (36%) of those with an IQ of less than 50. A significant difference was found between the 47 individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…No significant change in time from epilepsy onset to surgery over the study period was observed in this study which is unfortunate as a short duration of epilepsy has been shown to predict an improved developmental trajectory [4][5][6][7][8][9]. This further emphasises the importance of early referral of children with early onset intractable epilepsy of suspected symptomatic aetiology for epilepsy surgery evaluation [26].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…No significant change in time from epilepsy onset to surgery over the study period was observed in this study which is unfortunate as a short duration of epilepsy has been shown to predict an improved developmental trajectory [4][5][6][7][8][9]. This further emphasises the importance of early referral of children with early onset intractable epilepsy of suspected symptomatic aetiology for epilepsy surgery evaluation [26].…”
Section: Discussionmentioning
confidence: 55%
“…As mentioned above, a bearing hypothesis in early resective surgery is that the disruption of uncontrolled seizure activity improves the postoperative neurodevelopmental trajectory. There is some evidence supporting this view but the studies suffer from methodological drawbacks (small cohorts, heterogeneous aetiologies, retrospective, crosssectional design, different methods of assessing neurodevelopment across studies) [4][5][6][7][8][9]. Consequently, further studies, preferably multi-centre, prospective and longitudinal, as pointed out by Beghi and Tonini, are needed to assess neurodevelopmental, behavioural and quality of life outcomes after epilepsy surgery in infants and young children [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, given the natural history of DRE with seizure onset in infancy (7), early surgical intervention is preferred, including relatively large resections or disconnections when indicated. In addition to seizure remission, it may be possible to avoid the financial burden and potentially harmful side effects of antiepileptic medications during early brain development (79)(80)(81)(82)(83)(84). Early surgery also takes advantage of increased neuroplasticity in infants, which rapidly decreases with age.…”
Section: Special Considerations: Infantsmentioning
confidence: 99%
“…In the past few decades, the outcome in terms of freedom from seizures has either tended to improve (Hemb et al 2010), or remained stable (Lamberink et al 2015) in large paediatric epilepsy surgery centres. Freedom from seizures has repeatedly been associated with favourable cognitive outcome (Puka et al 2017;Van Schooneveld & Braun 2013;Viggedal et al 2013), even with catch-up in mental development (Freitag & Tuxhorn 2005).…”
Section: Introductionmentioning
confidence: 99%